EP294/#883 Elimusertib, an oral ataxia telangiectasia and RAD3-related inhibitor, in advanced gynecologic cancers with DNA damage response defects. (4th December 2022) - Tan, David S; Castonguay, Vincent; Cote, Gregory; Bono, Johann S De; El-Rayes, Bassel; Gabrail, Nashat; Iwasa, Satoru; Joerger, Markus; Jones, Robert; Sawyer, Michael B; Shapiro, Geoffrey I; Tan, Daniel; et al.
Abstract : Objectives: Elimusertib is a potent, orally available, selective inhibitor of ataxia telangiectasia and Rad3-related kinase, a critical component of DNA damage response (DDR) machinery. We report elimusertib's safety and efficacy in patients with gynecologic cancers and DDR deficiencies enrolled in Phase I (NCT03188965 ). Methods: Advanced gynecologic cancer patients resistant or refractory to standard treatment received elimusertib 40 mg twice daily on a 3 days on/4 days off schedule. Results: 45 patients received ≥1 dose of elimusertib: 36 with ovarian, 7 with endometrial, and 2 with cervical cancer. 64% of patients had previously received ≥4 therapy lines. BRCA1, BRCA2, and ATM mutations were present in 60%, 20%, and 31% of patients, respectively. 58% of ovarian cancer patients were resistant to last platinum-based therapy and 69% had received PARP inhibitor (PARPi) treatment. Grade 3/4 drug-related treatment-emergent adverse events (TEAEs), mainly hematologic toxicities, were observed in 69%/20% of patients. Dose reduction/discontinuation due to drug-related TEAEs was reported in 40%/11% of patients. Overall response rate was 2% (1/44 evaluable); 77% of patients had a best response of stable disease. One ovarian cancer patient had a PR lasting 308 days (BRCA1). In ovarian cancer patients, the clinical benefit rate at 120 days was 40%, including patients with previous PARPi treatment; 19% of patients had ≥50% reduction in CA-125 levels. Conclusions: Elimusertib demonstrated clinical benefit in heavily pretreated gynecologic cancers with DDR defects, including platinum-resistant ovarian cancer with previous PARPi treatment. A Phase I study of elimusertib plus niraparib is ongoing (NCT04267939 ).